Modified amplitude adaptive control algorithm for power quality improvement in multiple distributed generation system - Kewat, Seema; Singh, Bhim (IET power electronics, 2019)
This study deals with the modified amplitude adaptive notch filter (AANF)-based control algorithm for managing the generated power from different energy sources in an autonomous microgrid. In this study, the autonomous microgrid consists of a wind energy conversion system, photovoltaic array and a storage battery. The main objective of the proposed modified AANF (MAANF)-based control algorithm is to control the flow of active and reactive powers among the different energy sources and the load, along with the regulation of the point of common coupling (PCC) voltages and mitigation of the source current harmonics. The advanced features of proposed control algorithm are the DC-offset rejection from the input signal and fast frequency estimation, which enable the MAANF control algorithm to rapidly and accurately estimate the fundamental components of the distorted load currents. Therefore, the estimated reference source currents remain immune to the DC offset and various harmonic currents. The active power balance is achieved by regulating the DC-link voltage using a bidirectional DC–DC converter, which is connected between the DC link of the voltage source converter and a storage battery. Test results have validated the control algorithm under various steady-state and dynamic operating conditions.